Deriving temperature and age appropriate heart rate centiles for children with acute infections. Issue 5 (19th November 2008) - Thompson, M; Harnden, A; Perera, R; Mayon-White, R; Smith, L; McLeod, D; Mant, D
Abstract : Objectives: To describe the reference range for heart rate in children aged 3 months–10 years presenting to primary care with self-limiting infections. Design: Cross-sectional study of children presenting to primary care with suspected acute infection. Heart rate was measured using a pulse oximeter and axillary temperature using an electronic thermometer. Centile charts of heart rates expected at given temperatures for children with self-limiting infections were calculated. Setting: Ten general practice surgeries and two out-of-hours centres in England. Participants: 1933 children presenting with suspected acute infections were recruited from in-hours general practice surgeries (1050 or 54.3%) or out-of-hours centres (883 or 45.7%). After excluding children who subsequently attended hospital and those without a final diagnosis of acute infection, 1589 children were used to create the centile charts of whom (859 or 54.1%) had upper respiratory tract infections and (215 or 13.5%) non-specific viral illness. Main outcome measures: Median, 75th, 90th and 97th centiles of heart rate at each temperature level. Results: Heart rate increased by 9.9–14.1 bpm with each 1°C increment in temperature. The 50th, 75th, 90th and 97th centiles of heart rate at each temperature level are presented graphically. Conclusions: Age-specific centile charts of heart rates expected at different temperatures should be used by clinicians in the initial assessment of children with acute infections. The charts will identify children who have a heart rate higher than expected for a given temperature and facilitate the interpretation of changes in heart rate on reassessment. Further research on the predictive value of the centile charts is needed to optimise their diagnostic utility.